PENERAPAN METODA TAGUCHI SEBAGAI USULAN PERBAIKAN KUALITAS DALAM MENGHADAPI PERMASALAHAN CACAT PADA PRODUK BOTOL MORNING FRESH (LIME) ISI 1000 ML DI CV. TUNGGAL JAYA PLASTICS - Hari Adianto; Yeny Agustin; Yogi Yusuf Wibisono (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
One of the company efforts in increasing the sales volume of a product is with maintaining and increasing the quality of a product that have been produce by the company. Therefore, it is very important for the company to analyze and identify the problems that have been caused during the production process so the company can increase the quality of the product and productivity. Problems that cause during analyzing the defect product in production is how to arrange the optimal setting from each factor that significantly related so the company can minimize the defect product. This research was done at CV Tunggal Jaya Plastics and took the Morning Fresh (Lime) 1000 ml case product. Taguchi method is one of the methods that can be used to minimize the defect product by applying robust system for uncontrollable factors. The final result is to know factors that related significantly to the defect product and suggest the level of each factor therefore the defect product can be minimized.